ANALISA DAMPAK PENAMBANGAN TERHADAP ALIRAN SUNGAI - Martini, Sri; Kimi, Sudirman (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2017)
Lematang Riveris the longest riverin the province ofSouthSumatra, with a length of159kmand theflowarea of7340km²watershed. Natural resourcesare veryabundantminesinLahat.Materialsproduction centersandsandquarryin thevillageLower Market.Purposeof this studywas to determinehow bigthe impact ofmining activitiesthat affectchanges incross-sectional area, allowing theimpact ontheriverflow. From the analysis resultsobtainedcalculationdischargethe past 10 yearsmining130,01m³/sec, debitwithoutmining130,01m³/secanda flow rate of1.030m/sec.